Penerapan Model PBL Berbantuan Video Youtube untuk Meningkatkan Hasil Belajar Siswa Kelas II SDN 01 Srondol Kulon - Marsum Guriadi; Muhammad Fathunnabila; Tegar Firgiawan; Kurotul Aeni; Nur Indah Wulandari; Muhammad Syaifu Anshori (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to determine the extent to which the Civics learning outcomes of class 2 students at SDN 01 Srondol Kulon have improved on the subject of Obeying Rules at School and in the Surroundings using the Problem Based Learning learning model. The research subjects were 21 class 2 students. This research was carried out in two cycles consisting of 2 meetings in cycles 1 and 2. The first cycle used the application or web, namely Quizizz Papermode, with material about obeying school regulations and for the second cycle, the application or web, Quizizz Papermode, was used with different material, namely obeying rules around us. Based on data on students' activeness and responsibility in participating while taking part in learning, it has increased from cycle 1 to cycle 2. And based on the research results, the average value of student learning outcomes is 72 in cycle 1 and 81 in cycle 2. Completeness of learning outcomes from The initial condition reached 62% and in cycle 1 there was an increase, namely 76% and 100% in cycle 2. It was concluded that the Problem Based Learning learning model using YouTube media could improve the Civics learning outcomes of class 2 students at SDN 01 Srondol Kulon.